Spatial analysis of vocational education services in the city of Baghdad - Hassan, Fouad (Al-Adab Journal, 2024)
Vocational education is one of the most important branches of education due to its contribution to the preparation of intermediary cadres, which is the main driver of commercial, agricultural, industrial and service projects, as it plays an important role in supporting the development process as it appears clear on the national economy and the accompanying support for progress The civilization of the country, this research focused on the spatial analysis of vocational education in the city of Baghdad at the level of its districts and determining the extent to which each district needs this service, as this model of education is of great importance because of its direct connection with development and the need of the market.